Monitoring: a fundamental functionality for orchestrating services on Fog Computing - Costa, Breno; Araújo, Aletéia P. F. (Anais da Escola Regional de Alto Desempenho do Centro-Oeste (ERAD-CO), 2021)
Fog Computing is a distributed paradigm that provides computational resources in the users' vicinity. To provide services to the users, take place the orchestration of fog resources and services, a set of functionalities that coordinate the dynamic infrastructure and take actions to guarantee the SLAs agreed. Monitoring is an orchestration functionality of prime importance. It is the basis for resource management actions, collecting resources status and providing the data needed to an adequate management. This work proposes a monitoring architecture for fog computing environments that addresses the needs for an adequate fog resource and service orchestration.